INDONESIAN CHILDREN PROTECTION POLICY AS A PREVENTION OF SEXUAL EXPLOITATION THROUGH SOCIAL MEDIA - Ikhsan, Ikhsan; Pujiyono, Pujiyono (Tadulako Law Review, 2020)
Besides offering various facilities and economic benefits, globalization also has many negative impacts. Commercial sexual exploitation of children is one of the negative impacts caused by the current of globalization. Sexual exploitation of children is currently experiencing developments influenced by globalization, one of which is the sexual exploitation of children through online media or social media. In some cases in Indonesia, sexual exploitation of children through social media is usually done through live broadcasts called by the term â€œvidsex (video sex)â€ or â€œvidcallsex (video call sex)â€ which is interpreted as a live video call for sexual scenes. Therefore this normative study wants to examine the Indonesian governmentâ€™s policy efforts as a preventive effort in tackling the sexual exploitation of children through social media. The results of this study indicate that the regulation as a preventive measure for the protection of children against sexual exploitation of children through social media has generally been regulated in legislation such as the Child Protection Law and the Information and Electronic Transaction Law.